Effects of emotional valence and arousal on acoustic duration reproduction assessed via the “dual klepsydra model” - Wackermann, Jiri; Meissner, Karin; Tankersley, Dharol; Wittmann, Marc (Frontiers in Neurorobotics, 2014)
We report results of an acoustic duration reproduction task with stimulus duration of 2, 4 and 6 s, using 45 emotionally negative, positive, and neutral sounds from the International Affective Digitized Sounds System, in a sample of 31 young healthy participants. To investigate the influence of induced emotions on perceived duration, the effects of emotional modulation were quantified in two ways: (i) via model-free indices (aggregated ratios of reproduced times), and (ii) via dual klepsydra model (DKM)-based estimates of parameters of internal time representation. Both data-analytic approaches reveal an effect of emotional valence/arousal, namely, a significantly longer reproduction response for emotional stimuli than for the neutral stimuli. The advantage of the DKM-based approach is its ability to disentangle stimulus-related effects, which are represented by ‘flow intensities’, from general effects which are due to the lossy character of temporal integration. We explain the rationale of the DKM-based strategy and interpret the observed effect within the DKM framework as transient increase of internal ’flows’. This interpretation is in line with recent conceptualizations of an ‘embodiment’ of time where the model-posited flows correspond to the ongoing stream of interoceptive (bodily) neural signals. Neurophysiological findings on correlations between the processing of body signals and the perception of time provide cumulative evidence for this working hypothesis.